Genetic differentiation and structuring of Pugal and Garole sheep - MISHRA, BINA; TANTIA, M S; VIJH, R K (The Indian Journal of Animal Sciences, 2011)
The microsatellite data analysis of 22 heterologous loci in Pugal and Garole sheep breed found in 2 different geographical regions revealed 122 alleles with 45 alleles as private. 26 alleles of Pugal and 19 alleles of Garole breed were peculiar to the breed. The mean number of alleles were 4.68 and 4.52 with observed heterozygosity values of 0.648 and 0.683, respectively, for the 2 breeds. The FIS values were negative indicating no structuring in the populations. The population differentiation value based on analysis of molecular variance was 10.8%, and the high value can be attributed to large geographical distance between the breeding tracts of the 2 breeds. All the individuals could be assigned to their respective populations based on log likelihood values with 100% accuracy. Bayesian analysis revealed one cluster for Pugal while substructuring existed in Garole breed owing to peculiar nature of breeding tract. The interindividual distances estimated using allele sharing and Nei’s standard genetic distance and the Neighbor Joining tree constructed from these distances revealed distinctive grouping of the individual belonging to 2 breeds. The existence of genetic substructures in Garole sheep shall require different conservation strategies as there has been little gene flow among different islets as revealed in the present study.